OsUGE3‐mediated cell wall polysaccharides accumulation improves biomass production, mechanical strength, and salt tolerance. (29th May 2022) - Tang, Yijun; Wang, Meihan; Cao, Liyu; Dang, Zhengjun; Ruan, Nan; Wang, Ye; Huang, Yingni; Wu, Jiayi; Zhang, Mingfei; Xu, Zhengjin; Chen, Wenfu; Li, Fengcheng; et al.
Abstract: Cell walls constitute the majority of plant biomass and are essential for plant resistance to environmental stresses. It is promising to improve both plant biomass production and stress resistance simultaneously by genetic modification of cell walls. Here, we report the functions of a UDP‐galactose/glucose epimerase 3 (OsUGE3) in rice growth and salt tolerance by characterizing its overexpressing plants ( OsUGE3‐OX ) and loss‐of‐function mutants ( uge3 ). The OsUGE3‐OX plants showed improvements in biomass production and mechanical strength, whereas uge3 mutants displayed growth defects. The OsUGE3 exhibits UDP‐galactose/glucose epimerase activity that provides substrates for polysaccharides polymerization, consistent with the increased biosynthesis of cellulose and hemicelluloses and strengthened walls in OsUGE3‐OX plants. Notably, the OsUGE3 is ubiquitously expressed and induced by salt treatment. The uge3 mutants were hypersensitive to salt and osmotic stresses, whereas the OsUGE3‐OX plants showed improved tolerance to salt and osmotic stresses. Moreover, OsUGE3 overexpression improves the homeostasis of Na + and K + and induces a higher accumulation of hemicelluloses and soluble sugars during salt stress. Our results suggest that OsUGE3 improves biomass production, mechanical strength, and salt stress tolerance by reinforcement of cell walls with polysaccharides and it could be targeted for genetic modification to improve rice growth under salt stress. Summary Statement: Genetic improvement of cell walls is a promising way to improve both biomass production and stress resistance. The OsUGE3 catalyzes the bioconversion between UDP‐Gal and UDP‐Glc, which increases the biosynthesis of cell wall polysaccharides and soluble sugars, and thus strengthens cell walls in rice, leading to improvements in biomass production, mechanical strength, and salt tolerance.